Representation of Local Cultural Identity in Batik Carnival: A Socio-Semiotic Analysis of Visual Expressions in the Sendangagung Community - Angga Fajar Ramadhan; Syakir Syakir; Djuli Djatiprambudi; Muhammad Ibnan Syarif (LP2M ISBI Bandung, 2026)
This study aims to examine the representation of the local cultural identity of coastal communities in batik carnival costumes as a form of visual cultural expression constructed and negotiated amidst the currents of globalization. The study was conducted in Sendangagung Village, Paciran District, Lamongan Regency, using a socio-semiotic approach that focuses on the analysis of signs, symbols, visual elements, and the production of cultural meaning in batik carnival costumes. The results show that the Sendangagung Batik Carnival event functions as a medium for representing coastal cultural identity, constructed through an encoding process in the form of the natural environment and the social life of the local community. The resulting meaning is not static but is formed through a process of decoding signs constructed by the audience. This study contributes to enriching socio-semiotic studies, especially in viewing visual cultural practices as a strategic medium for representing local identity amidst the currents of globalization.